Feed-forward active noise control system using microphone array - Liu, Lichuan; Li, Yang; Kuo, Sen M. (IEEE/CAA journal of automatica sinica, 2018)
Feedforward active noise control &#x0028 ANC &#x0029 system are widely used to reduce the wide-band noise in different application. In feedforward ANC systems, when the noise source is unknown, the misplacement of the reference microphone may violate the causality constraint. We present a performance analysis of the feedforward ANC system under a noncausal condition. The ANC system performance degrades when the degree of noncausality increases. This research applies the microphone array technique to feedforward ANC systems to solve the unknown noise source problem. The generalized cross-correlation &#x0028 GCC &#x0029 and steering response power &#x0028 SRP &#x0029 methods based on microphone array are used to estimate the noise source location. Then, the ANC system selects the proper reference microphone for a noise control algorithm. The simulation and experiment results show that the SRP method can estimate the noise source direction with 84&#x0025 accuracy. The proposed microphone array integrated ANC system can dramatically improve the system performance.